Cognitive‐behavioral screening in elderly patients with new‐onset epilepsy before treatment. (3rd May 2014) - Witt, J.‐A.; Werhahn, K. J.; Krämer, G.; Ruckes, C.; Trinka, E.; Helmstaedter, C.
<x xml:space="preserve">Abstract</x> Objectives Cognitive comorbidity at epilepsy onset reflects disease severity and provides a baseline estimate of reserve capacities with regard to the effects of epilepsy and its treatment. Given the high incidence of epilepsy at an older age, this study analyzed objective and subjective cognition as well as quality of life in elderly patients with new‐onset focal epilepsy before initiation of anti‐epileptic treatment. Materials and methods A total of 257 untreated patients (60–95 years of age) with new‐onset epilepsy underwent objective assessment of executive function (EpiTrack) and performed subjective ratings of cognition (Portland Neurotoxicity Scale) and quality of life (QoL; QOLIE‐31). Results According to age‐corrected norms, 58% of patients (N = 257) demonstrated deficits in executive function; major determinants were cerebrovascular etiology, neurological comorbidity, and higher body mass index. Subjective ratings indicated deficits in up to 27% of patients. Self‐perceived deficits were associated with neurological, cardiovascular, and/or psychiatric comorbidity, whereas poorer QoL was related to neurological comorbidity and female gender. Objectively assessed executive functions correlated with subjective social functioning, energy, motor function, and vigilance. Conclusions We found a relatively high QoL, a low rate of subjective impairment, but a high incidence of objective executive deficits in untreated elderly patients with new‐onset epilepsy. Neurological status and body mass index, rather than seizure frequency or severity, were risk factors for cognitive impairment. Given the relevance of cognition in the course of epilepsy and its treatment, routine screening before treatment initiation is highly recommended.